Theoretical modeling of adiabatic and non-adiabatic two-phase flows in a capillary tube - Liang, Shao Min. (2008)
Capillary tubes are commonly used to meter the refrigerant flow from the high pressure (condenser side) to the lower pressure (evaporator side) in small refrigeration systems, such as household refrigerators and freezers, dehumidifiers and room air-conditioners. This simple device consists of a long copper tube with internal diameters ranging from 3.3x 1CT4 to 1.5 x 10-3 m and lengths from 1.5 to 5.0 m.